Muscle metabolism during sprint exercise in man: Influence of sprint training - Barnett, C.; Carey, M.; Proietto, J.; Cerin, E.; Febbraio, M. A.; Jenkins, D. (Journal of Science and Medicine in Sport, 2004)
In order to examine the influence of sprint training on metabolism and exercise performance during sprint exercise, 16 recreationally-active, untrained, men (VO2peak= 3.8+/-0.1 l.min(-1)) were randomly assigned to either a training (n= 8) or control group (n= 8). Each subject performed a 30-sec cycle sprint and a test to measure VO2peak before and after eight weeks of sprint training. The training group completed a series of sprints three times per week which progressed from three 30-sec cycle sprints in weeks 1 and 2, to six 30-sec sprints in weeks 7 and 8. Three mins of passive recovery separated each sprint throughout the training period. Muscle samples were obtained at rest and immediately following the pre- and post-training sprints and analysed for high energy phosphagens, glycogen and lactate; the activities of both phosphofructokinase (PFK) and citrate synthase (CS) were also measured and muscle fibre types were quantified. Training resulted in a 7.1% increase in mean power output (p<0.05), an 8% increase in VO2peak (p< 0.001), a 42% increase (p< 0.01) in CS activity and a 17% increase (p< 0.05) in resting intramuscular glycogen content. In contrast, neither PFK activity nor fibre type distribution changed with training. An increase (p< 0.05) in mean power output and attenuated (p< 0.01) ATP degradation were observed during sprint exercise following training. Glycogen degradation during sprint exercise was unaffected by sprint training. These data demonstrate that sprint training may have enhanced muscle oxidative but not glycolytic capacity.